Evaluation of Patient Satisfaction BPJS Outboard with Pharmaceutical Services in Pharmaceutical Installations RSUD Dr. M.M Dunda Limboto - Mustapa, Alinda; Supu, Rini Daud; Daud, Serly; Moha, Lidya Paramita (LPPM Universitas Bina Mandiri Gorontalo, 2022)
This study aims to find out the level of satisfaction of outpatient BPJS patients to pharmaceutical services in the pharmaceutical installation of Dr. M.M DundaLimboto Hospital which is seen based on five dimensions, namely reliability dimension, responsiveness dimension, assurance dimension, tangible dimension, and empathy dimension. The type of this research is descriptive observational quantitative with a cross sectional research approach. The sources of data in this study are BPJS Rajal patients who receive pharmaceutical services at the Pharmacy Installation of RSUDdDr. M.M, DundaLimboto, with data obtained via filling out a questionnaire for each respondent, using five assessment scores, very satisfied 5, satisfied 4, quite satisfied 3, dissatisfied 2, and dissatisfied 1. The method used in the current studywas the customer satisfaction index (CSI) method aiming at knowing the level of customer satisfaction. The results show that the satisfaction of outpatient BPJS patients to pharmaceutical services at the pharmaceutical installation of Dr. M.M DundaLimboto Hospital is 79.93% categorized as satisfied.